Juridical Review of Seller's False Information in Villa Sale and Purchase Transactions Resulting in Consumer Losses Based on Law No. 8. Year 1999 concerning Consumer Protection - Monica Dian Ekasari; Yuniar Rahmatiar; Muhamad Abas (Dinasti Research, 2024)
False information is any information that is deliberately conveyed with the aim of misleading or manipulating the recipient of the information. This practice can occur under consumer protection law, including in advertising, selling products or services, and various other forms of communication. False information often goes against the principles of honesty, transparency and integrity in communication. The case that occurred in decision number 57/Pdt.G/2021/PN.Cbi was the sale of a villa or called Villa NE-21. The practice of buying and selling Villa NE-21 was carried out not according to procedures, namely providing false information to consumers, this is serious violations of consumer protection principles and applicable laws. This research adopts two main methods, namely normative juridical and analytical descriptive approaches. PPJB NE-21 which has been signed by the plaintiff and defendant can be said to be null and void due to false information carried out by the seller in the sale and purchase transaction of Villa NE-21. According to the author's analysis, the verdict read out by the panel of judges is in accordance with statutory provisions. In article 19 of the UUPK it is explained that business actors must be responsible for all forms of losses experienced by consumers, and the form of responsibility carried out by business actors can be converted into money.